Developing Web Based Learning Media Using Wordpress in Light Material at SMP/MTS - Pajrianor, Pajrianor; Supriatin, Atin; Syar, Nur Inayah; Annovasho, Jhelang (JIPF (Jurnal Ilmu Pendidikan Fisika), 2024)
The purpose of this research was to find out the result of development and feasibility of web based learning media in light material. The method used in this research was Research and Development (R&D) with 4D development model namely the stage of define, design, develop, and disseminate. The subjects of this study were material expert validators, media expert validators, teachers and 26 students at Islamic Junior High School (MTS) of Darul Ulum Palangkaraya. This research gained the result namely first, the media developed in the form of web based learning media in light material has components such as menu, animation picture, practice simulation, example of question, glossary, and evaluation question which can be accessed through website via online. The second, the feasibility of web based learning media seen from the suitability measured through media validation, material validation, teachers’ response, and students’ response. The result of media validation gained total average score 80 in excellent criteria. The result of material validation gained average score 76,5 in excellent criteria. The result of teacher’s response on web based teaching material gained total score 67 in excellent criteria. The result of students’ response concerning the web based teaching material gained total score 36,52 in excellent criteria. Based on the results of the study, it can be implied that this web-based teaching material is valid and can be used to improve the quality of student learning.